Financial development and investment dynamics in Mauritius: A trivariate Granger-causality analysis - Brian Muyambiri; Nicholas M. Odhiambo (SPOUDAI - Journal of Economics and Business, 2018)
This paper examines the causal relationship between both bank-based and market-based financial development and investment in Mauritius for the period from 1976 to 2014. The study assumes that investment and financial development have an accelerator-enhancing relationship. To accommodate the accelerator-enhancing relationship, the indicators for bank-based and market-based financial development are multiplied by the per capita GDP. In addition, to avoid variable omission bias, savings are used as an intermittent variable, thereby creating a trivariate Granger-causality model. The study makes use of the autoregressive distributed lag bounds testing approach. For both models, results indicate that both bank-based and market-based financial development Granger-cause investment, both in the short run and in the long run. The study, therefore, recommends that policies in Mauritius should focus mainly on promoting and strengthening banking sector and stock market development in order to spur investment.
Keywords: G10; G20; E22; 330; Mauritius; Investment; Bank-based financial development; Market-based financial development